HUBUNGAN KEBIASAAN BELAJAR DI MASA PANDEMI COVID 19 DENGAN HASIL BELAJAR MATA PELAJARAN GAMBAR TEKNIK PESERTA DIDIK KELAS X SMKN 1 KOTO XI TARUSAN - Ramadhanus, Arien Jonika; Apdeni, Risma (Jurnal Applied Science in Civil Engineering, 2023)
Arien Jonika Ramadhanus, 2023 : The Relationship between Study Habits during the Covid 19 Pandemic and Learning Outcomes in the Technical Drawing Subject of Class X Students of SMKN 1 Koto XI Tarusan Education is very important for human life. Humans need education in order to continue their lives, therefore every human being has the right to education. A high level of education will produce quality human resources, so as to achieve the goal of education itself, namely to form Indonesian people who have better personalities. This survey research was conducted by distributing questionnaires offline. The research was conducted on students of Engineering Drawing subject class X for the 2020-2022 Academic Year, SMKN 1 Koto XI Tarusan. West Sumatra Province, Pesisir Selatan District, Koto XI Tarusan District. The research sample was taken as many as 52 students of Class X SMKN 1 Koto XI Tarusan. The results of the study showed that there was a relationship between study habits and student learning outcomes in Engineering Drawing class X for the 2020- 2022 Academic Year, SMKN 1 Koto XI Tarusan. the higher the student's study habits, the better the learning outcomes and vice versa students who have low study habits will also get low learning outcomes. Study habits are behaviors that are repeated and become a characteristic of a person in carrying out learning tasks both at school and at home.